Segmental kick velocity is correlated with kick specific and nonspecific strength performance in a proximodistal sequence - Moreira, Pedro Vieira Sarmet [UNESP]; De Paula, Leandro Vinhas; Veloso, António Prieto (My University, 2015)
Background & Study Aim: Explosive strength and vertical jump performance have typically been associated with fast unloaded movements, however their relationship with the martial kick velocity has not been studied. The purpose of this study was to answer the question if kick velocity is correlated with kick specific and nonspecific strength performance, in a proximodistal sequence. Material & Methods: Six male black-belt taekwondo athletes (20.5 ± 4.3 years, 67.1 ± 4.8 kg, 1.78 ± 0.06 m, 21.378 ± 1.9) were evaluated for various strength indicators isometrically, through an adapted Leg Press machine, and dynamically, through Counter Movement Jump (CMJ) over a force platform, in ground reaction force (GRF), in linear peak velocities (PV) and time to reach PV (tPV) of lower body segments, during kick, through 3D kinematic analysis at 200 samples/second. Kinematic indicators of kick performance were compared between segments, and then, each kinetic parameter was correlated with them. After, the nonspecific strengt parameters were correlated with those specific force parameters that firstly had significant correlation with at least one parameter of velocity. The alpha level of significance was p <0.05. Results: Th ere were significant differences of timings and velocities between segments. Aditionally, there were significant correlations between specific horizontal GRF and nonspecific strength indicators, especially for CMJ, with the velocities of leg segments during the kick. Conclusion: The results indicated that, segmental kick velocity is associated with isometric and stretch shortening cycle performance, but modulated by ground reaction force production in a proximodistal sequence.
Keywords: Ballistic velocity; Explosive strength; Martial arts; Sport performance; Vertical jump